Use of a new milk-clotting protease from Thermomucor indicae-seudaticae N31 as coagulant and changes during ripening of Prato cheese - Merheb-Dini, Carolina [UNESP]; Garcia, Graziele Aparecida Chiuchi [UNESP]; Penna, Ana Lúcia Barretto [UNESP]; Gomes, Eleni [UNESP]; Da Silva, Roberto [UNESP] (Elsevier, 2012)
Prato cheeses were manufactured using coagulant from Thermomucor indicae-seudaticae N31 or a commercial coagulant. Cheeses were characterised using the following analysis: yield; fat; acidity; moisture; ash; salt; pH; total nitrogen; total protein; NS-pH 4.6/NT100; NS-TCA 12%/NT100; casein electrophoresis; and RP-HPLC. The results were statistically analysed and revealed that the proteolytic indices were not significantly different throughout the 60 days of ripening of cheeses made with either coagulant. Even though there were some quantitative differences in the peptide profile of cheeses, the enzyme from T. indicae-seudaticae N31 was used in the production of good quality Prato cheese without having to change the established technological parameters of the process. © 2011 Elsevier Ltd. All rights reserved.
Keywords: Commercial coagulant; Milk-clotting enzyme; Prato cheese; Proteolysis; Thermomucor indicae-seudaticae N31; Peptide profile; RP-HPLC; Technological parameters; Total nitrogen; Total protein; Electrophoresis; Enzymes; Coagulation; casein; fat; nitrogen; proteinase; sodium chloride; acidity; ash; cheese; cheese ripening; electrophoresis; fungus; high performance liquid chromatography; milk; moisture; protein degradation; Thermomucor indicae; Thermomucor indicae-seudaticae